Pengaruh TAnggung Jawab Sosial Perusahaan (Corporate Social Responsibility) Terhadap Profitabilitas dan Nilai Perusahaan Pada Perusahaan Manufaktur di Indonesia - Kurniawati, Lintang; Kholis, Nur (Graduasi: Jurnal Bisnis & Ekonomi, 2013)
The purpose of this study is to obtain empirical evidence whether corporate social responsibility has influence on the profitability of the company by ROA and ROE , and it influence on the value of the company reflected by market value and is measured by TobinsQ.The population of this study is manufacturing companies listed in Indonesia Stock Exchange in the period 2008-2010. Samples were taken by using purposive sampling and obtained 108 company for three years (36x3) that match the criteria. Because the data is not normal at the beginning of the testing performed data reduction for data containing outliers (extreme data), so that samples can be processed into 71. Technique analysis using classical assumption test and linear regression analysis. To help analyze the data, the authors using SPSS 17 for windows.The results showed that social responsibility reveal any significant effect on profitability by ROA and ROE and influence also the value of the company is reflected in this study by TobinsQ.